Tafsir Falsafi: Pemetaan Tipologi, Epistemologi dan Implementasi - Husnul Hakim, Ahmad; Ahmad, Amiril (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2022)
Philosophy and interpretation are two studies that come from different sides. When these two sciences are used to understand the Qur’an, the Quranic exegesis that has a philosophical character emerges. This research tries to trace the various intersections between Islamic philosophy and tafsir, especially in the frame of typology, epistemology, and implementation. The results of this study indicate that the emergence of the style of philosophical interpretation came through the translation of Greek works into Arabic. In general, there has not been found a complete Qur’anic commentary that contains philosophical style and is mostly found separately through writings that do not specifically interpret the Qur'an. The epistemology of the early generation of philosophical interpretations leaned towards paripathetic, thus involving the use of reason in discussing verses about divinity, life after death, and also scientific knowledge since nearly all philosopher scholars were also scientists. This article will more clearly examine some philosophers who explain some verses of the Qur’an with a philosophical approach including: al-Kindi, al-Farabi, Ikhwan al-Shafa, and Ibn Sina.